Lexical Hedges in Mamma Mia! Movie - Septiarini, Ni Ketut Ani; Suastra, I Made; Putra, I Komang Sumaryana (Humanis, 2021)
The study is aimed to generally identify the types of lexical hedges used in the movie script and to determine the function of lexical hedges used. The data of this study were taken by using documentation method and note-taking technique from the movie Mamma Mia! , which firstly released in 2008. The movie is originally conducted by Phyllida Lloyd and also written by Catherine Johnson based on the 1999 musical of the same name, which is based on the songs of famous pop group ABBA. The data were analyzed descriptive qualitatively using Lakoff’s theory about women’s language features (1973). This study revealed that there were four examples of lexical hedges found in Mamma Mia! movie.